Fourier coefficients of functions from the classes B and C. Parseval equality for the class C or for the Fourier-Stieltjes series - Konyushkov, A. A. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
We study restrictions that should be imposed on the numbers sequences {α_n} and {Β_n} in order to guarantee that the series olimits_n = 1^∞ a_n nx and olimits_n = 1^∞ b_n nx do not belong to the classes B or C for any a n and b n such that a_n ≥ α_n, b_n ≥ Β_n, n = 1, 2.